Syntheses, structures and properties of group 12 element (Zn, Cd, Hg) coordination polymers with a mixed-functional phosphonate-biphenyl-carboxylate linker. Issue 27 (3rd June 2016) - Heering, Christian; Francis, Biju; Nateghi, Bahareh; Makhloufi, Gamall; Lüdeke, Steffen; Janiak, Christoph
Abstract : Layers of metal–oxygen polyhedra are interconnected via the biphenyl linker to create hydrolytically stable 3D coordination or supramolecular networks. Abstract : The new phosphonate-carboxylate ligand from 4-phosphono-biphenyl-4′-carboxylic acid (H2 O3 P–(C6 H4 )2 –CO2 H, H3 BPPA) is based on the rigid biphenyl system and is studied toward the coordination behavior of group 12 elements zinc, cadmium and mercury. The crystalline products from hydrothermal syntheses highlight the versatile and different coordination modes with the (partially) deprotonated H3 BPPA ligand to give coordination polymeric 3D-[Zn5 (μ3 -OH)4 (μ4 -O3 P–(C6 H4 )2 –CO2 -μ2 )2 ] n (5 ), 2D-[Zn(μ6 -O3 P–(C6 H4 )2 –CO2 H)] n (6 ), 3D-[Cd3 (μ5 -O3 P–(C6 H4 )2 –CO2 -μ2 )(μ6 -O3 P–(C6 H4 )2 –CO2 -μ3 )] n (7 ) and 2D-[Hg(μ3 -HO3 P–(C6 H4 )2 –CO2 H)] n (8 ). The cobalt complex, 2D-[Co(μ4 -O3 P–(C6 H4 )2 –CO2 H)] n (9 ) is isostructural to6 . Through additional classic strong carbonyl O–H⋯O hydrogen bonding the dimensionality of the 2D coordination networks increases to 3D supramolecular frameworks. The carboxy-phosphonate ligand shows five different coordination modes which can be described as μ4 -O3 P–CO2 -μ2 (5 ), μ6 -O3 P– (6 ), μ5 -O3 P–CO2 -μ2, μ5 -O3 P–CO2 -μ3 (7 ), and μ3 -O3 P– (8 ), that is, the ligand bridges altogether between 3 to 8 metal atoms with the phosphonate group alone connecting already 3 to 6 metal atoms. Layers of metal–oxygen polyhedra are interconnected via the biphenyl linker, which either coordinates metal atoms with both donor groups or the –COOH end forms tail-to-tail hydrogen bonds to create 3D or 2D coordination networks, respectively. In the flat MO x layers in6 and7 the Zn and Cd metal nodes represent a honeycomb and anmcm net, respectively. The coordination polyhedra of the Cd atoms in compound7 were analyzed towards a trigonal-prismatic coordination environment. The complexes are hydrolytically very stable due to their hydrothermal preparation from aqueous solution at 180–200 °C. The compounds could be stored in water or air for months without apparent decomposition. Compounds5 and7, where the ligand is fully deprotonated, start to decompose at ∼400 °C. The fluorescence emission spectrum of the ligand, 4, shows an intense peak at 365 nm ( λ ex = 316 nm). The fluorescence emission of the metal complexes5, 7 and9 is shifted towards larger wavelengths with values of 417 nm, 415 nm and 410 nm, respectively ( λ ex = 354 nm for5, λ ex = 350 nm for7, λ ex = 400 nm for8, λ ex = 360 nm for9 ). In addition, the crystal structures of the H3 BPPA ligand precursors 4-iodo-4′-biphenylcarboxylic acid methyl ester, and 4-diethylphosphono-4′-biphenylcarboxylic acid methyl ester are described here for the first time.